Pengembangan Lembar Kerja Peserta Didik (LKPD) Untuk Meningkatkan Keterampilan Literasi Sains Peserta Didik Pada Materi Laju Reaksi - Iktifaul Ulya; Rusmini Rusmini (PendIPA Journal of Science Education, 2022)
The purpose of this development research was to describe the feasibility of student worksheet to improve students scientific literacy skills on the reaction rate material in terms of aspects of validity, practicality, and effectiveness. The research method refers to the 4-D development model by Thiagarajan which is limited to the develop stage with limited trials to students of class XI science at SMA Negeri 1 Gedangan as many as 30 students. The results of data analysis showed that the feasibility of LKPD from the aspect of validity seen from 4 criteria, namely content, presentation, language, and graphics, the percentage was 93.72%; 93.33%; 90.28%; and 92.78% with very valid criteria. The practicality of LKPD seen from the observation of activities and student response questionnaires obtained a percentage of 98.69% and 95.91% on very practical criteria. The effectiveness of the LKPD is seen from the results of the students pretest and posttest, namely cognitive tests and tests of scientific literacy skills which showed an increase with N-Gain scores of 0.67 and 0.60 in the medium category, respectively. LKPD to improve proper scientific literacy skills is very important to be developed as a learning resource so that it makes the learning process of students meaningful.